A qualitative study of occupational stress management techniques of personal assistants in Durban North - Creed, Tayla (My University, 2020)
Stress can have a significant effect on the employee’s performance, and their psychological health, including burnout, increased amount of “sick days”, anxiety etc. (Volmink, 2014; Van Zyl, 2002). There is much literature on occupational stress in occupations such as engineering (Rothmann & Malan, 2004), and the educational sector (Botwe, Kenneth, Masih, 2017), yet the work of personal assistants has not been sufficiently investigated. The research problem is that there are many ways of dealing with stress, such as relaxation, and exercise (Fokeng, 2018). However, not knowing how to destress can lead to problematic outcomes which important to study as personal assistant can be overlooked. This study considers the South African context, which has not been explored in most literature. Three participants were approached and semi-structured interviews were conducted to allow participants to share their personal lived about their stressors, stress management techniques, and reasons why those techniques work best for them. This research is underpinned by Lazarus and Folkman’s theory, and through the concepts such as stressor, and stress management, and it has been found that there might not be an exact way personal assistants manage their stress, but rather manage their stress, according to their personality.
Keywords: Occupational stress; Stress management; Personal assistants; Techniques